Validation of Owenia vieitezi Díaz-Díaz, Parapar & Moreira, a polychaete from the coast of Venezuela (Annelida: Oweniidae) - Díaz-Díaz, Oscar Felipe; Parapar, Julio; Moreira, Juan (Zootaxa, 2020)
Díaz-Díaz et al. (2018) described a new species of oweniid polychaete, Owenia vieitezi, from the north-western coast of the Gulf of Venezuela, Caribbean Sea. Although the description and figures presented by Díaz-Díaz et al. (2018) fully characterize the new species, the journal issue in which the description appeared was published online only and the article in which the new name appeared did not include a ZooBank registration number (LSID), required for validation of new species names in electronic-only publications (ICZN 2012). As a result, the name Owenia vieitezi Díaz-Díaz, Parapar & Moreira, 2018, as published in Cahiers de Biologie Marine 59: 589–597, is not available according the International Code of Zoological Nomenclature (ICZN 1999, 2012). Therefore, the present note serves to validate the name Owenia vieitezi by fulfilling the ICZN conditions for nomenclatural availability.